Bringing an Intersectional Lens to "Open" Science: An Analysis of Representation in the Reproducibility Project. (December 2021) - Sabik, Natalie J.; Matsick, Jes L.; McCormick-Huhn, Kaitlin; Cole, Elizabeth R.
Feminist psychologists have called for researchers to consider the social and historical context and the multidimensionality of participants in research studies. The Reproducibility Project documents the degree to which the findings from mainstream psychological studies are reproduced. Drawing on intersectionality theory, we question the value of reproducing findings while ignoring who is represented, intersecting social and group identities, sociohistorical context, and the power and privilege that likely influence participants' responses in psychology experiments. To critically examine the Reproducibility Project in psychology, we analyzed the 100 replication reports produced between 2011 and 2014 (Open Science Collaboration, 2015). We developed an intersectional analytic framework to investigate (a) representation, (b) whether demographic and identity factors were considered through a multidimensional or intersectional lens, (c) explanations of non-replication, and (d) whether socio-cultural context was considered. Results show that reports predominantly include WEIRD samples (people from Western, educated, industrialized, rich, and democratic countries). Context and identity were rarely considered, even when study design relied on these factors, and intersectional identities and structures (considering power, structural issues, discrimination, and historical context) were absent from nearly all reports. Online slides for instructors who want to use this article for teaching are available on PWQ's website athttp://journals.sagepub.com/doi/suppl/10.1177/03616843211035678